Respuesta :

we know that

The volume of the prism is equal to

[tex]V=L*W*H[/tex]

where

L is the length side of the base of the prism

W is the width side of the base of the prism

H is the height of the prism

In this problem we have

[tex]L=\frac{d-2}{3d-9}=\frac{d-2}{3(d-3)}[/tex]

[tex]W=\frac{4}{d-4}[/tex]

[tex]H=\frac{2d-6}{2d-4}=\frac{2(d-3)}{2(d-2)}=\frac{(d-3)}{(d-2)}[/tex]

Substitute the values in the formula

[tex]V=\frac{d-2}{3(d-3)}*\frac{4}{d-4}*\frac{(d-3)}{(d-2)}=\frac{4}{3(d-4)}=\frac{4}{3d-12}[/tex]

therefore

the answer is the option

[tex]\frac{4}{3d-12}[/tex]


Answer:

Option C is correct

[tex]\frac{4}{3d-12}[/tex]

Step-by-step explanation:

Using the formula:

[tex]V = lwh[/tex]

where,

l is the length of the prism

w is the width of the prism

h is the height of the prism.

As per the statement:

From the given figure:

Length of the prism(l) = [tex]\frac{d-2}{3d-9}[/tex]

Width of the prism(w) = [tex]\frac{4}{d-4}[/tex]

Height of the prism(w) = [tex]\frac{2d-6}{2d-4}[/tex]

Substitute these in [1] we have;

[tex]V = \frac{d-2}{3d-9} \cdot \frac{4}{d-4} \cdot \frac{2d-6}{2d-4}[/tex]

[tex]V = \frac{d-2}{3(d-3)} \cdot \frac{4}{d-4} \cdot \frac{2(d-3)}{2(d-2)}[/tex]

⇒[tex]V = \frac{1}{3} \cdot \frac{4}{d-4} \cdot \frac{2}{2}[/tex]

Simplify:

⇒[tex]V = \frac{4}{3(d-4)}[/tex]

⇒[tex]V = \frac{4}{3d-12}[/tex]

Therefore, the expression for the volume of the following prism is, [tex]\frac{4}{3d-12}[/tex]